Theory, policy, pratice : development and discontents in India - Nath, Suman; Bhattacharya, Debraj (Abingdon, Oxon ; New York, NY : Routledge, 2022)
This book explores the meanings and perceptions of development and the dialectics of theory, policy and practice. It looks at how theory translates into policy, and the disconnections in its design and implementation in the Indian context. The book focuses on the influence of capitalist globalisation, democratisation, decentralisation and neoliberal economic reforms on the development discourse in India and how these have challenged the traditional role of the state', the meaning of citizenship, and public participation. Through an analysis of case studies from various parts of the country, it bridges the gap between policy prescriptions and practices and unpacks the institutional, political and policy-led compulsions and incompatibilities which most often remain unreported. It also discusses the intersections between policymaking and the politics of class, caste and gender, and emphasises the role bureaucracy plays in institutional governance. The volume includes articles from professionals ranging from academics, practitioners and activists. It will be of interest to scholars and researchers of public policy, development studies, South Asian politics, and economics as well as policy makers and practitioners in government and civil society.
OCLC-licensed vendor bibliographic record.
Keywords: Economic development -- India -- 21st century; SOCIAL SCIENCE / General; POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / Public Policy / Social Policy